Optimization of SARS-CoV-2 laboratory testing in a rural healthcare facility in the United States - Bharathan, Tanvi S.; Trale, Austan J.; Bharathan, Tashi; Dienes, Nichol L.; Sansig, Jackie; Wilson, Steven; Bharathan, Narayanaswamy (International Journal Of Community Medicine And Public Health, 2021)
Background: The diagnostic testing for SARS-COV-2 (COVID-19) presented a profound challenge to the entire world, dominating the concern of most governments and public health systems, particularly rural community hospitals in the United States. Indiana University of Pennsylvania (IUP) in partnership with Indiana Regional Medical Center (IRMC) began on site, same-day COVID-19 testing in efforts to not only combat the challenges that health providers faced in rural Indiana community but also help to strengthen global diagnostic capacity. Methods: Clinical samples were collected as dry swabs from the nasopharyngeal (NP) regions and processed in phosphate buffer saline (PBS). The crude RNA was directly tested using real-time (RT) reverse transcription quantitative polymerase chain reaction (RT-qPCR) with PrimeDirect probe RT-qPCR Mix (Takara Bio USA) and optimized with probe-primer sets [Integrated DNA Technologies (IDT)]. Results: Validation experiments with dry swabs from NP clinical samples showed no difference in the testing accuracy to those collected in viral transport medium or universal transport medium. Extraction of COVID-19 RNA in PBS reduced processing time of a batch of 50 NP clinical samples from 6 hours to an hour. This allowed for rapid diagnostic testing of nearly 200 clinical samples per day. Optimization of analytical variables helped to detect virus loads up to 2.0 copies/μl during routine diagnostic testing. Conclusions: During an infectious outbreak, the ideal response by public health authorities is rapid testing. The collaboration between IUP and IRMC attests to the importance of teamwork between local initiatives to detect and prevent further spread within a rural community.